Catalyzed production of different grade biofuels using metal ions modified activated carbon of cellulosic wastes. (1st July 2021) - Altalhi, Amal A.; Mohammed, Eslam.A.; Morsy, Salwa. Salwa M.; Negm, Nabel.A.; Farag, Ahmed A.
Graphical abstract: Highlights: Activated carbon of cellulosic waste (ACCD) was prepared by carbonization process. The chemical activation of ACCW with Mn 2+ and/or Fe 3+ was carried out using an impregnation method. Catalytic cracking process of WCO using the prepared catalysts (ACCD, ACCD/Mn, and ACCD/Fe). Characterization of the produced biofuel was established according to ASTM standard specifications. The engine tests showed that the thermal brake efficiency of the blend B10 was closed to the petroleum diesel. Abstract: This work aims to convert waste cooking oil (WCO) into biofuel through a catalytic cracking process. The process of catalytic cracking was catalyzed using activated carbon loaded with iron and manganese ions. Cellulosic waste, as an eco-friendly, cheap, and renewable resource, was used to prepare the activated carbon. FTIR, XRD, TGA, differential thermal analysis, and N2 -adsorption/desorption investigations were applied to characterize the prepared catalysts. Characterization of the obtained biofuels was established according to ASTM standard specifications. The engine tests of the different blends of biofuels-traditional diesel were performed. The obtained data confirmed that the biofuel blend contained 10% biofuel (B10) decreased the brake-specific fuel consumption from 651 g/kw.h for regular diesel to 554 g/kw, and raised the thermal brake efficiency from 15% to 17.4%. Therefore, a biofuel-petroleum fuel blend at 10% of biofuel can be presented as a promising fuel blend for the petroleum diesel.